2014
DOI: 10.14348/molcells.2014.0008
|View full text |Cite
|
Sign up to set email alerts
|

RNA Binding Protein-Mediated Post-Transcriptional Gene Regulation in Medulloblastoma

Abstract: Medulloblastoma, the most common malignant brain tumor in children, is a disease whose mechanisms are now beginning to be uncovered by high-throughput studies of somatic mutations, mRNA expression patterns, and epigenetic profiles of patient tumors. One emerging theme from studies that sequenced the tumor genomes of large cohorts of medulloblastoma patients is frequent mutation of RNA binding proteins. Proteins which bind multiple RNA targets can act as master regulators of gene expression at the post-transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 104 publications
(172 reference statements)
2
17
0
Order By: Relevance
“…In our study, we found that FENDRR and MDR1 3 0 UTR contain several AU-rich elements (AREs) sequences, which interact with RNA-binding protein (RBP), suggesting that FENDRR and MDR1 may be subjected to post-transcriptional regulation. Previous studies have indicated that RBP can bind to ARE sequences of mRNA for stabilizing and/or regulating their translation [44]. On the basis of our findings, we confirmed that HuR can stabilize the mRNA of FENDRR and MDR1.…”
Section: Discussionsupporting
confidence: 87%
“…In our study, we found that FENDRR and MDR1 3 0 UTR contain several AU-rich elements (AREs) sequences, which interact with RNA-binding protein (RBP), suggesting that FENDRR and MDR1 may be subjected to post-transcriptional regulation. Previous studies have indicated that RBP can bind to ARE sequences of mRNA for stabilizing and/or regulating their translation [44]. On the basis of our findings, we confirmed that HuR can stabilize the mRNA of FENDRR and MDR1.…”
Section: Discussionsupporting
confidence: 87%
“…For example, ENDOG, mutated in family B (p.R111fs), is a DNase involved in mediating caspase-independent apoptosis 21. DDX31, a RNA-binding protein mutated in family C (p.L367fs), is frequently mutated in medulloblastoma,22 and a germline truncating mutation was observed in a patient with sporadic CRC 23. Family D carries a RGS19 nonsense mutation (p.Q89X), a gene involved in regulating G-protein signalling and autophagy in intestinal cells 24.…”
Section: Resultsmentioning
confidence: 99%
“…RBPs participate in multiple post-transcriptional regulations, such as RNA splicing, stability and degradation 42 43. Accordingly, they might serve as potential mediators of ceRNA activity in several ways.…”
Section: Mechanisms and Molecular Bases Of Cerna Interplaymentioning
confidence: 99%